Structural Analysis in the Novel Renaissance by Kinoysan - Nida Firdaus Albanjari; Akmaliyah; Niqyatul Muna; Nurmeila Adawiah Mubarokah (Aksis : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2024)
This study analyzes the structure in the novel entitled "Renaissance" by Kinoysan. This study aims to analyze and describe the structure in the novel "Renaissance". The building structures that will be discussed in this novel include theme, plot, characters and characterization, setting, point of view and moral. This study uses a qualitative descriptive method. In obtaining data in this novel, it is necessary to use reading and listening techniques. The data source in this study is a novel entitled "Renaissance" by Kinoysan. Researchers are interested in analyzing this novel because the theme of the story in the novel raises the issue of romance and family. From the results of the analysis of the novel "Renaissance" by Kinoysan, data were obtained in the form of theme, plot, characters and characterization, setting, point of view and moral. Each data is in accordance with its division.